2020
DOI: 10.1002/cplu.201900349
|View full text |Cite
|
Sign up to set email alerts
|

A Zirconium Indazole Carboxylate Coordination Polymer as an Efficient Catalyst for Dehydrogenation‐Cyclization and Oxidative Coupling Reactions

Abstract: Rational ligand design is crucial for achieving widespread applications of coordination polymers. The preparation, structural characterisation, and catalytic applications of zirconium (IV) coordination polymer (Zr-IDA), which was derived from 1-(carboxymethyl)-1H-indazole-5-carboxylic acid are reported. The Zr-IDA catalyst contains porous and highly crystalline particles with a quasi-spherical morphology around 100 nm in size, and Zr was coordinated with both O and N as shown by FT-IR and XPS measurements. Imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 118 publications
0
15
0
Order By: Relevance
“…67,68 Recently, Wang and co-workers prepared a CP of zirconium indazole carboxylate (Zr-IDA) and investigated Zr-IDA-promoted dehydrogenation−cyclization of 2 and alcohol with KOH as a strong base at a reaction temperature of 110 °C for the syntheses of 1,2-disubstituted benzimidazole derivatives. 69 In our case, C−TiO 2 /1 (600) functions as a photocatalyst and catalyzes the dehydrogenation−cyclization of 2 and ethanol at an ambient temperature in the absence of a base under visible light irradiation, thus demonstrating an environmentally friendly route for benzimidazole synthesis with the C−TiO 2 /1 (600) catalyst. Moreover, Wang et al reported a mesoporous [Ru(bpy) 3 ] 2+ (bpy = 2,2′-bipyridine) ligandbased porous organic polymer (Ru-POP) and examined photosynthesis of 2-phenyl-benzimidazole from 2 and benzaldehyde with Ru-POP as the catalyst.…”
Section: Methodsmentioning
confidence: 99%
“…67,68 Recently, Wang and co-workers prepared a CP of zirconium indazole carboxylate (Zr-IDA) and investigated Zr-IDA-promoted dehydrogenation−cyclization of 2 and alcohol with KOH as a strong base at a reaction temperature of 110 °C for the syntheses of 1,2-disubstituted benzimidazole derivatives. 69 In our case, C−TiO 2 /1 (600) functions as a photocatalyst and catalyzes the dehydrogenation−cyclization of 2 and ethanol at an ambient temperature in the absence of a base under visible light irradiation, thus demonstrating an environmentally friendly route for benzimidazole synthesis with the C−TiO 2 /1 (600) catalyst. Moreover, Wang et al reported a mesoporous [Ru(bpy) 3 ] 2+ (bpy = 2,2′-bipyridine) ligandbased porous organic polymer (Ru-POP) and examined photosynthesis of 2-phenyl-benzimidazole from 2 and benzaldehyde with Ru-POP as the catalyst.…”
Section: Methodsmentioning
confidence: 99%
“…As typically important bioactive heterocyclic compounds, benzimidazoles have been extensively investigated for their broad spectrum in biological and pharmacological activities in antibacterial, antifungal, antiviral, anti‐inflammatory, anti‐ulcer, antihypertensive, antihistamine, antitumor, anticancer, and anti‐HIV [39–44] . Therefore, various synthetic methods were developed [45–48] . However, these synthetic processes generally suffer from various limitations such as the use of strong acidic reaction medium, toxic solvents, high reaction temperature, reactive reagent, strong dehydrating agent, oxidizing agent, and noble metal catalysts [49–54] .…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41][42][43][44] Therefore, various synthetic methods were developed. [45][46][47][48] However, these synthetic processes generally suffer from various limitations such as the use of strong acidic reaction medium, toxic solvents, high reaction temperature, reactive reagent, strong dehydrating agent, oxidizing agent, and noble metal catalysts. [49][50][51][52][53][54] For example, the most traditional method for 2-phenyl-1H-benzo[d]imidazole (4 a) synthesis involves condensation of 1,2-phenylenediamine (2) with benzaldehyde (3 a, Scheme 1a), [55] whereas 2 is industrially obtained by 2-nitroaniline (1 a) reduction.…”
Section: Introductionmentioning
confidence: 99%
“…In this reaction, various aromatic alcohols could be converted to the corresponding benzimidazoles in mediocre yields.T he amount of Cu leaching after five ). [51] H 2 IDA is synthesized from the reaction of 1H-indazole-5-carboxylate,m ethyl 2-bromoacetate,a nd anhydrous potassium carbonate in MeCN.A fter ZrCl 4 and H 2 IDAwere dissolved in DMF/HOAc,t he resulting solid is separated by filtration, washed with DMF and EtOH, and heated at 80 8 8Cf or 5hto afford Zr-IDA( Figure 14). This heterogeneous catalyst displayed high catalytic activity in the synthesis of 1,2-disubstituted benzimidazole derivatives from o-phenylenediamines and aromatic alcohols at 110 8 8C.…”
Section: Non-noble Metal-based Heterogeneous Catalystsmentioning
confidence: 99%